Maternal depression and child development: A prospective analysis of consequences, risk and protective factors - Roetner, Jakob; Petry, Janna; Niekamp, Julia; Maschkel, Janina; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; Moll, Gunther; Eichler, Anna (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2022)
Maternal depression and child development: A prospective analysis of consequences, risk and protective factors Abstract. Objective: Maternal stress, specifically maternal mental health problems, are considered risk factors for child development. The literature suggests that prenatal depressive symptoms as well as depressive symptoms are a widespread phenomenon during the further development of the child and have repeatedly been shown to have adverse effects on child mental health outcomes. The present study examined the longitudinal relationships between maternal depression (prenatal, postnatal, during childhood and adolescence) and child mental health from childhood to adolescence. Possible risk and protective factors were also considered. Method: N = 112 mothers were assessed for depressive symptoms via a questionnaire at four different timepoints (prenatal, T1; postnatal, T2; during childhood, T3; during adolescence, T4). Children's externalizing and internalizing symptoms (50.9 % girls) were assessed by their mothers both during childhood (M = 7.68, SD = 0.76 years) and during adolescence (M = 13.23, SD = 0.27 years). We evaluated the relationships between maternal depressive symptoms and children's externalizing/internalizing symptoms using multiple regression models and analyzed possible risk and protective factors using moderation analysis. Results: Externalizing/Internalizing symptoms were not directly associated with maternal depressive symptoms, while associations between such symptoms and maladaptive behavior were found in adolescents. The socioeconomic status of families showed a different risk profile for prenatal and postnatal depressive symptoms. The IQ of the children proved to be a risk factor for internalizing symptoms. Conclusions: Maternal depressive symptoms at any time during child development - in combination with further risk factors - have an impact on child mental health. The early identification of maternal symptoms followed by interventions to differentiate between prenatal and postnatal depression - especially in the context of socioeconomic status - are highly relevant for child development.
CRIS-Team WoS Importer:2022-04-08
Keywords: Pränatale Depressivität; kindliche Erlebens- und Verhaltensauffälligkeiten; Risiko- und Schutzfaktoren; sozioökonomischer Status; Intelligenzquotient; Prenatal depression; child behavior; risk and protective factors; socioeconomic status; intelligence quotient